Bifunctional peptides as alternatives to copper-based formulations to control citrus canker - Dilarri, Guilherme; de Lencastre Novaes, Leticia Celia; Jakob, Felix; Schwaneberg, Ulrich; Ferreira, Henrique [UNESP] (Springer Nature, 2024)
Abstract: Citrus canker is an infectious bacterial disease and one of the major threats to the orange juice industry, a multibillion-dollar market that generates hundreds of thousands of jobs worldwide. This disease is caused by the Gram-negative bacterium Xanthomonas citri subsp. citri. In Brazil, the largest producer and exporter of concentrate orange juice, the control of citrus canker is exerted by integrated management practices, in which cupric solutions are intensively used in the orchards to refrain bacterial spreading. Copper ions accumulate and are as heavy metals toxic to the environment. Therefore, the aim of the present work was to evaluate bifunctional fusion proteins (BiFuProts) as novel and bio-/peptide-based alternatives to copper formulations to control citrus canker. BiFuProts are composed of an anchor peptide able to bind to citrus leaves, and an antimicrobial “killer” peptide to protect against bacterial infections of plants. The selected BiFuProt (Mel-CgDEF) was bactericidal against X. citri at 125 μg mL−1, targeting the bacterial cytoplasmic membrane within the first minutes of contact. The results in the greenhouse assays proved that Mel-CgDEF at 250 μg mL−1 provided protection against X. citri infection on the leaves, significantly reducing the number of lesions by area when compared with the controls. Overall, the present work showed that the BiFuProt Mel-CgDEF is a biobased and biodegradable possible alternative for substitute cupric formulations. Key points: • The bifunctional fusion protein Mel-CgDEF was effective against Xanthomonas citri. • Mel-CgDEF action mechanism was the disruption of the cytoplasmic membrane. • Mel-CgDEF protected citrus leaves against citrus canker disease.
Keywords: Anchor peptide; Citriculture defensive; Citrus leaf-binding; Melittin; Xanthomonas citri